Phytochemical Screening and In Vivo Antimalarial Activity of Two Traditionally Used Medicinal Plants of Afar Region, Ethiopia, against Plasmodium berghei in Swiss Albino Mice - Sibhatu Gebrehiwot; Mohammed Shumbahri; Amelework Eyado; Tilahun Yohannes (Journal of Parasitology Research)
The objective of the present study was to investigate phytochemical components, antiplasmodial activity (in vivo) and evaluate the toxicity of two local medicinal plants, namely, Salvadora persica L. and Balanites rotundifolia (Van Tiegh.) used in Afar ethnomedicine for the treatment of malaria. In this study, phytochemical screening has been done using standard methods and the existence of antiplasmodial compounds was detected in these plant extracts. Four-day Peter’s test was used to determine parasite inhibition, PCV was determined by Wintrob’s method, and effects against loss of body weight and improvements on survival time were determined. LD50s of the crude extracts have been also done. Acute toxicity studies of the extracts were carried out in Swiss albino mice prior to antimalarial activity test. All extracts revealed no obvious acute toxicities on mice up to the highest (5000mg/kg) dose given. The crude extract was estimated to have oral median lethal dose higher than 5,000 mg/kg. With the 4-day suppressive test, both plant extracts demonstrated dose-dependent significant reduction in parasitemia level at all test doses compared to the negative control: in the extract of B. rotundifolia 500 mg/kg extract (60.59±3.25%), 350 mg/kg extract (48.1±1.4), and 200 mg/kg extract (41.33±1.1%) were found. And in case of S. Persica 500 mg/kg extract (50.6±4.01%), 350 mg/kg extract (35.85±0.89), and 200 mg/kg extract (27.69±1.14%) were found. The results of this study provide support for the traditional therapeutic value and the reported antimalarial activity.